К тpaктoвкe английских рефлексивов - Генюшене, Э. (Kalbotyra, 1978)
This paper concerns itself with the question whether English reflexives should be considered as free word-combinations, reflexive verbs, a reflexive voice, or phraseological units. In view of their heterogeneity no single solution For all reflexives is considered acceptable. It is argued that the reflexives may be classified into free word-combinations, reflexive verbs and phraseological units on the basis of the semantic relation between the components.